Skills for a modern entrepreneur or business owner - Premaratne, Pasan; Sharon, Tomer; Armstrong, Hope; Gorgone, Dan; Chapman, C. C.; Watson, Michael; Deitch, Ben; Menge, Julie (Packt Publishing, 2024)
In today's competitive business world, success requires more than just a great idea. This course guides you through the essentials of modern entrepreneurship, from the basics of starting a business to scaling and sustaining it. You'll learn how to identify customer segments, develop a strong value proposition, and analyze industry dynamics. The course covers key areas like business planning, market research, and financial analysis, equipping you with the tools to make informed decisions. You'll also explore advanced topics, including digital marketing, data analysis, and financial statements, ensuring a well-rounded understanding of business management. Additionally, the course emphasizes soft skills and leadership, helping you develop the confidence and strategic insight necessary to lead your business to success. Whether you're an aspiring entrepreneur or a current business owner, this course provides actionable strategies and practical knowledge to thrive in today's dynamic marketplace. By the end, you'll be prepared to navigate the challenges of entrepreneurship with a clear vision and the skills needed for growth.
Online resource; title from title details screen (O'Reilly, viewed September 16, 2024)
Keywords: Entrepreneurship -- Handbooks, manuals, etc; Entrepreneuriat; Guides, manuels, etc; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet